COMPARATIVE LAW ANALYSIS OF THE REGULATION OF PROCEDURAL COSTS UNDER THE LEGISLATION OF RUSSIA, BELARUS AND KAZAKHSTAN - DEKHERT Andrey Andreevich (Правовое государство: теория и практика, 2024)
The institution of procedural costs in Russia since the adoption of the Criminal Procedure Code of the Russian Federation has been subject to minor changes, which may indicate either that it is perfect or the legislator has forgotten about it. In the meantime, some issues that arise periodically for law enforcement officials (for example, the recovery of procedural costs from the heir of a deceased accused) remain without the necessary attention of the legislator or the highest judicial authority. Given that the decision on the distribution of procedural costs is mandatory in the operative part of any judgement, special attention should be paid to the institution of procedural costs. Purpose: to review trends in the development of norms on procedural costs in the legislation not only of the Russian Federation, but also of foreign countries with similar legal systems. The paper aims to formulate proposals to improve the national legislation on the basis of the analysis of the legislation of the Republic of Belarus and the Republic of Kazakhstan. The methodological basis of the study is the comparative law method. General scientific methods of analysis are used, as well as the methods of legal interpretation and logicallegal. Results: the conducted research allows to identify differences in approaches to solving general issues of legal regulation of procedural costs in the legislation of Russia, Belarus and Kazakhstan. The use of the comparative law method in studying the theoretical and practical aspects of the institution of procedural costs in the legislation of different countries leads to the conclusion that specific provisions on procedural costs should be established, resulting from overcoming the opposition to criminal prosecution, as well as the decision on the fate of procedural costs in accepting the inheritance by heirs of a dec eased accused.